Mesocorticolimbic monoamines in a rodent model of chronic neuropathic pain - Cunha, A. M.; Guimarães, M. R.; Kokras, N; Sotiropoulos, I; Sousa, N.; Almeida, A.; Dalla, C; Leite-Almeida, H (Neurosci Lett, 2020)
Chronic pain manifests in multiple disorders and is highly debilitating. While its pathophysiology is not fully understood, the involvement of the mesocorticolimbic monoaminergic systems have been shown to play a critical role in chronic pain emergence and/or maintenance. In this study, we analyzed the levels of monoamines dopamine (DA), noradrenaline (NA) and serotonin (5-HT) in mesocorticolimbic areas - medial prefrontal cortex, orbitofrontal cortex, striatum, nucleus accumbens and amygdala - 1 month after a neuropathic lesion, Spared Nerve Injury (SNI). In SNI animals, were observed a marginal decrease of DA and 5-HT in the striatum and a rightward shift in the levels of NA in the nucleus accumbens. While mesocorticolimbic monoamines might be relevant for chronic pain pathophysiology its content appears to be relatively unaffected in our experimental conditions.
Keywords: Amygdala/*metabolism; Animals; Corpus Striatum/*metabolism; Dopamine; Dopamine/*metabolism; Frontal Lobe/*metabolism; Laterality; Male; Neuralgia/*metabolism; neuropathy; Noradrenaline; Norepinephrine/*metabolism; Nucleus Accumbens/*metabolism; Rats; Rats, Wistar; Serotonin; Serotonin/*metabolism; Striatum